Judicial Beginnings: The Supreme Court in the 1790s - Frankel, Robert P., Jr. (History compass, 2006)
There has long been a tendency to mark the beginning of the Supreme Court's history with the appointment of John Marshall as chief justice in 1801. But as the volumes of The Documentary History of the Supreme Court of the United States, 1789-1800 have exhibited, the first decade of the Court's life deserves significant attention. In the 1790s the Court asserted its autonomy, played an important role in setting the federal-state balance, and, prior to Marbury v. Madison, exercised the authority of judicial review. The justices who sat on the Court in its first decade essentially shared the views of the two presidents who appointed them, George Washington and John Adams, but made it clear that the judiciary did not exist to serve either the executive or the legislature.